Ion-imprinted cellulose-based aerogel material for extracting uranium from seawater and preparation method thereof
Ion-imprinted cellulose-based aerogel materials prepared by cellulose nanofibers, sodium periodate and polyethyleneimine solve the problem of insufficient performance of existing seawater uranium extraction materials, and achieve efficient uranium extraction, reusability and Anti-biological fouling properties reduce costs.
Patent Information
- Application Number
- CN202311154780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The comprehensive performance of existing seawater uranium extraction materials (uranium extraction speed, adsorption selectivity, mechanical properties and pollution resistance) is poor, resulting in limited in actual applications, and insufficient economic costs and pollution resistance.
Ultralight aerogels are prepared using cellulose nanofibers, sodium periodate and polyethyleneimine. Through ionic blotting of uranium-containing solution and covalent chemical crosslinking of epoxychlorohydrin, it forms excellent uranium extraction ability and reusing Ion-blot cellulose-based aerogel material with high mechanical properties.
It has achieved efficient uranium extraction in simulated seawater, significantly improved adsorption capacity, good reusability, strong anti-biological fouling, excellent mechanical properties, and significantly reduced the cost of uranium extraction in seawater.
Smart Images

Figure CN117019116B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater and a preparation method thereof. Background Art
[0002] The ocean contains abundant uranium resources. The world's seawater contains 4.5 billion tons of uranium, which is 1,000 times the reserves of uranium mines on land. The efficient extraction of uranium resources in seawater is of great significance to the development of marine energy and the sustainable development of human ecological environment. The current methods of extracting uranium from seawater are divided according to the principle, including adsorption, extraction, membrane separation, chemical precipitation, biological treatment, ion exchange, superconducting magnetic separation, etc. Among various materials, the most widely used are amidoxime-based materials. Due to the significant affinity and selectivity of amidoxime groups for uranyl ions, they are considered to be the most promising uranyl adsorption groups. For example, Chinese patent CN201910017858.1 discloses a water-soluble amidoxime-based polymer and its preparation method and application, and Chinese patent CN202010378458.6 discloses a method for preparing antibacterial amidoxime aerogel for extracting uranium from seawater, etc. Although a certain uranium extraction effect is achieved, there are problems such as poor mechanical properties and insufficient anti-fouling ability. Due to the extremely low uranium concentration in seawater, the excessive number of coexisting interfering ions and the harsh marine environment, the extraction of uranium from seawater by adsorbents faces huge challenges. In addition, the high economic cost and lack of anti-fouling ability have also seriously hindered the practical application of adsorbents. The development of existing adsorbents mainly focuses on solving one or several major problems, while adsorbents with comprehensive optimization characteristics are relatively scarce. This is mainly because adsorbents are often prepared in the form of composite materials, and the addition of new materials may cause a decrease in another property while imparting or enhancing a certain property, making it difficult to take both into account at the same time. In addition, although some seawater uranium extraction materials (such as metal organic framework materials, covalent organic framework materials, etc.) have relatively excellent performance, they cannot be recycled in actual seawater uranium extraction applications due to their powdered form.
[0003] Therefore, it is necessary to develop an ion-imprinted cellulose-based aerogel material and a preparation method for uranium extraction from seawater. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing ion-imprinted cellulose-based aerogel materials for uranium extraction from seawater, so as to solve the problem that the existing uranium extraction materials have poor comprehensive performance (uranium extraction speed, adsorption selectivity, mechanical properties and anti-fouling ability, etc.) which limits their application in actual seawater uranium extraction.
[0005] The present invention adopts a method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater, comprising the following steps:
[0006] S101: The cellulose nanofiber suspension is sequentially oxidized with sodium periodate and cross-linked with polyethyleneimine, and then freeze-dried to obtain CNF-OP aerogel;
[0007] S102: adding CNF-OP aerogel to a uranium-containing solution and shaking, then adding epichlorohydrin and reacting at 60° C. for 4 hours, and then eluting the uranyl ions to obtain ion-imprinted CNF aerogel, wherein the mass ratio of epichlorohydrin to CNF-OP aerogel is 5.
[0008] Preferably, the mass concentration of the cellulose nanofibers is 1 wt %, and the volume is 10 mL.
[0009] Preferably, the amount of sodium periodate added is 0.024 g and the stirring time is 30 min.
[0010] Preferably, the polyethyleneimine solution is 0.14 g, the mass concentration is 50 wt %, and the stirring time is 30 min.
[0011] Preferably, the concentration of the uranium-containing solution is 2.5 g L -1 , the volume is 20mL.
[0012] Preferably, the eluent is a mixed solution of 1 M sodium carbonate and 0.1 M hydrogen peroxide.
[0013] On the other hand, an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater is provided.
[0014] The preparation method of the ion-imprinted cellulose-based aerogel material provided by the present invention uses cellulose nanofibers, sodium periodate and polyethyleneimine to prepare ultra-light aerogel, and then uses uranium-containing solution ion imprinting and subsequent epichlorohydrin covalent chemical cross-linking, and uses the synergistic effect of precisely pre-organized coordination functional groups and immobilized coordination space structures to prepare the ion-imprinted cellulose-based aerogel material having the following advantages:
[0015] (1) Excellent uranium extraction capability: 1269.25 mg g in simulated seawater containing 128 ppm uranium -1 High adsorption capacity;
[0016] (2) Reusability: After 10 consecutive adsorption-desorption processes, the elution rate and uranium adsorption capacity of I-CNF aerogel decreased by only 0.96% and 3.22%, respectively.
[0017] (3) High adsorption selectivity: the distribution coefficient K of I-CNF aerogel D is 3.62×10 6 mL g -1 , the adsorption capacity of I-CNF aerogel for uranium is 19.01 times that of vanadium;
[0018] (4) Anti-biofouling: The inhibition rates of I-CNF aerogel against marine mixed bacteria, Escherichia coli, Staphylococcus aureus, Vibrio vulnificus and Pseudomonas mendocinae were 87.31%, 92.11%, 94.96%, 91.87% and 89.13%, respectively;
[0019] (5) Excellent mechanical properties: The maximum compressive stress reaches 165.51 kPa when the compressive strain is 80% in air; the maximum compressive stress reaches 41 kPa when the compressive strain is 80% in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the infrared spectrum of ion-imprinted cellulose-based aerogel material.
[0021] Figure 2 This is the X-ray photoelectron spectrum of ion-imprinted cellulose-based aerogel material.
[0022] Figure 3 This is a scanning electron microscope image of ion-imprinted cellulose-based aerogel material.
[0023] Figure 4 The figures are the test results of mechanical properties of ion-imprinted cellulose-based aerogel materials, where 4a represents the compressive stress-strain curve of I-CNF aerogel in air; 4b represents the stress-strain curve of I-CNF aerogel repeated for 50 cycles under 50% compressive strain; 4c represents the compressive stress-strain curve of I-CNF aerogel in water; 4d represents the compression and rebound properties of I-CNF aerogel in water.
[0024] Figure 5 The adsorption performance test results of ion-imprinted cellulose-based aerogel materials in simulated seawater containing uranium. 5a represents the effect of different pH on uranium adsorption capacity; 5b represents the adsorption kinetics and the corresponding fitting results; 5c represents the adsorption isotherm and the corresponding fitting results; 5d represents the effect of different eluents on the uranium elution rate of I-CNF aerogel after uranium adsorption; 5e represents the reusability of I-CNF aerogel; 5f represents the photos of I-CNF aerogel before and after elution and the uranium-containing eluent.
[0025] Figure 6 This is a test diagram of the antifouling ability of ion-imprinted cellulose-based aerogel materials, where 6a represents the antibacterial activity, Figure 6 b represents the inhibitory activity of aerogels against the tested bacteria.
[0026] Figure 7 The selective adsorption results of uranium in natural seawater by I-CNF aerogel and NI-CNF aerogel.
[0027] Figure 8Schematic diagram of the preparation of ion-imprinted cellulose-based aerogel materials. DETAILED DESCRIPTION
[0028] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0029] The cellulose nanofibers involved in the embodiments of the present invention were purchased from Shansi Technology, and sodium periodate, polyethyleneimine, epichlorohydrin and other reagents were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0030] Embodiment 1: A method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater, comprising the following steps:
[0031] S101: 10 mL of 1 wt% carbon nanofiber suspension was measured and vigorously stirred at 1000 rpm for 2 h; then 0.024 g of sodium periodate (NaIO3) was added and stirred for another 30 min in the dark; then 0.14 g of 50 wt% polyethyleneimine (PEI) was added to the mixture and stirred for 30 min; it was placed in a refrigerator at 4°C for 12 h to remove bubbles, and then freeze-dried to obtain CNF-OP aerogel;
[0032] S102: Weigh 0.1 g of CNF-OP aerogel from step S101 and add it to 20 mL of 2.5 g / L -1 uranium solution and shaken at 100 rpm for 24 h. E / C =5) 0.5 g of epichlorohydrin was added to the mixture and reacted at 60° C. for 4 h. The mixture was freeze-dried and then eluted with an eluent containing 1 M sodium carbonate and 0.1 M hydrogen peroxide to remove the uranyl ions. The freeze-dried mixture was ion-imprinted CNF aerogel (I-CNF aerogel).
[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that in step 102, the 20 mL concentration of 2.5 g / L -1 Ion-imprinting treatment of uranium solution was used to obtain non-ion-imprinted CNF aerosol (NI-CNF aerogel).
[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in step S101, the amount of sodium periodate and polyethyleneimine added and the stirring time are different, as shown in Table 1. The optimal experimental parameter combination was determined according to Table 1 and the adsorption performance was measured. When 0.024 g of sodium periodate was added and stirred for 30 min, and then 0.14 g of polyethyleneimine was added and stirred for 30 min, the prepared CNF-OP aerogel had the best uranium extraction performance of 527.97 mg g -1 .
[0035] Table 1 Effect of different treatment conditions on uranium adsorption of CNF-OP aerogel
[0036]
[0037] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the mass ratios of epichlorohydrin (ECH) and CNF-OP aerogel in step S102 are 0, 2.5, 7.5, 10, and 12.5, respectively. E / C With the increase of MR, the uranium adsorption performance and distribution coefficient of I-CNF aerogel first increased and then decreased. E / C Uranium extraction is best at 5 o'clock.
[0038] Table 2 Effect of different mass ratios of epichlorohydrin (ECH) and CNF-OP aerogel on uranium adsorption performance
[0039]
[0040] The ion-imprinted cellulose-based aerogel material for extracting uranium from seawater prepared in Example 1 was characterized and its performance tested:
[0041] (1) Structural characterization: Figure 1 The FTIR analysis results showed that the typical absorption peaks of carboxylated cellulose and Schiff base groups were detected in both NI-CNF aerogel and I-CNF aerogel, including COC (1063 cm -1 )、CO(1365cm -1 ), C=O(1597cm -1 ) and C=N(1630cm -1 ).like Figure 2 X-ray photoelectron spectroscopy (XPS) showed that only carbon, nitrogen and oxygen elements were detected in I-CNF aerogel and NI-CNF aerogel, further verifying the chemical composition of the two aerogels. In addition, there was no uranium element in I-CNF aerogel, indicating that the uranyl ions serving as ion-imprinted templates had been completely removed from the ion-imprinted adsorbent.
[0042] (2) Morphology test: Figure 3The scanning electron microscopy (SEM) results showed that compared with NI-CNF aerogel, I-CNF aerogel maintained a more ordered layered structure and a more evenly distributed pore structure. Its special spatial structure was conducive to the adsorption of uranyl ions. In addition, both I-CNF aerogel and NI-CNF aerogel exhibited ultra-light properties, which was helpful for their use and recycling in the practical application of uranium extraction from seawater.
[0043] (3) Mechanical properties test:
[0044] The compression and shape recovery properties of the aerogel were tested using a universal testing machine. Figure 4 The compression test of a showed that the compressive stress of ICNF aerogel increased rapidly with the increase of compressive strain, reaching a maximum compressive stress of 165.51 kPa at a compressive strain of 80%. The maximum compressive stress of I-CNF aerogel was higher than that of CNF and NI-CNF aerogel. Compared with existing cellulose-based aerogels, I-CNF aerogel has better mechanical properties. After 50 repeated compression cycles with a compressive strain of 50%, I-CNF aerogel still retained 94.17% of the initial compressive stress and showed a good shape recovery rate of 97.90%, indicating the superelasticity and structural stability of I-CNF aerogel ( Figure 4 b). This is mainly due to the ordered layered structure and porous structure of I-CNF aerogel, which realizes the effective transmission of compressive stress. In addition, I-CNF aerogel shows faster shape recovery ability in water than in air ( Figure 4 c and 4d), under the condition of compressive strain of 80%, I-CNF aerogel obtained a high compressive stress of 41 kPa in water, which is much better than the existing cellulose-based aerogels or natural sponges. Therefore, the excellent mechanical properties of I-CNF aerogel in water are conducive to its application in marine environment.
[0045] (4) Simulated seawater uranium extraction performance test:
[0046] High-efficiency uranium extraction performance: The results show that the uranium adsorption capacity of I-CNF aerogel is higher than that of NI-CNF aerogel in a wide pH range due to the ion imprinting process. Figure 5 a). In simulated seawater with a uranium concentration of 8 ppm and a pH of 6, the I-CNF aerogel and NI-CNF aerogel obtained 404.11 mg g -1 and 263.98mg g -1 Adsorption kinetics analysis showed that both I-CNF aerogel and NI-CNF aerogel reached adsorption equilibrium within 16 h, which is much shorter than the adsorption time of the most widely studied amidoxime-based adsorbents ( Figure 5b). Meanwhile, I-CNF aerogel achieved a uranium content of 249.97 mg g in simulated seawater with a uranium concentration of 8 ppm within 4 h. -1 The high uranium adsorption capacity of I-CNF aerogel was 14 h, while NI-CNF aerogel needed 14 h to achieve it, indicating that I-CNF aerogel has a faster adsorption rate than NI-CNF aerogel. The adsorption kinetics of I-CNF aerogel and NI aerogel both conformed well to the pseudo-second-order kinetic model, confirming that chemical adsorption is the main mechanism of uranium adsorption by these two aerogels. The adsorption isotherms in simulated seawater with uranium concentrations of 2, 4, 8, 16, 32, 64 and 128 ppm at pH 6.0 were also analyzed. I-CNF aerogel achieved 1269.25 mg g in simulated seawater with a uranium concentration of 128 ppm. -1 The high adsorption capacity of NI-CNF aerogel increased by 84.34% ( Figure 5 c) The theoretical maximum adsorption capacity of I-CNF aerogel calculated based on the Langmuir adsorption model is 1402.89 mg g -1 , much higher than other uranyl ion imprinted adsorbents.
[0047] Reusability: To explore the regeneration performance of the adsorbent, different eluents, including 0.1 M EDTA (pH 8.0), 0.1 M nitric acid, 0.5 M nitric acid, 0.1 M hydrochloric acid, 0.5 M hydrochloric acid, 0.1 M sodium hydroxide, and a solution containing 1 M Na2CO3 and 0.1 M H2O2, were used to remove the adsorbed uranium. Among these eluents, the solution containing Na2CO3 and H2O2 showed the highest elution rate of 98.64% for the I-CNF aerogel-bound uranium and was selected as the eluent for this study ( Figure 5 d). This eluent can elute about 92.52% and 98.64% of uranium bound by NI-CNF aerogel and I-CNF aerogel, respectively, within 5 min. It is worth noting that after 10 consecutive adsorption-desorption processes, the elution rate and uranium adsorption capacity of I-CNF aerogel only decreased by 0.96% and 3.22%, respectively. Figure 5 e and 5f), which is superior to NI-CNF aerogels and other uranyl ion imprinted adsorbents.
[0048] High selectivity:
[0049] Competition analysis between I-CNF aerogel and carbonate groups for uranyl ions showed that I-CNF aerogel had a high binding affinity for uranyl ions, K d The analysis of the binding selectivity in natural seawater spiked with 100 times metal ions showed that I-CNF aerogel achieved 19.54 mg g -1 The high uranium adsorption capacity and 1.93×10 5 mL g-1 High partition coefficient K D Compared with NI-CNF aerogel, I-CNF aerogel adsorbs fewer interfering metal elements, and the distribution coefficient K of I-CNF aerogel for uranium is D It is greatly improved, indicating that the ion imprinting process successfully endows I-CNF aerogel with high binding affinity and adsorption selectivity for uranyl ions.
[0050] Anti-Biofouling Performance:
[0051] The results of antibacterial experiments showed that compared with CNF aerogels, I-CNF aerogels showed significant inhibitory effects on marine mixed bacteria as well as Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Vibrio vulnificus (V. vulnificus) and Pseudomonas mendocina (P. mendocina). This was due to the presence of Schiff base groups in the aerogels, which led to enhanced membrane permeability of bacterial cells ( Figure 6 ). The inhibition rates of I-CNF aerogel against marine mixed bacteria, Escherichia coli, Staphylococcus aureus, Vibrio vulnificus and Pseudomonas mendocinae were 87.31%, 92.11%, 94.96%, 91.87% and 89.13%, respectively. This high antibacterial ability contributes to the application of I-CNF aerogel in natural seawater environment.
[0052] (5) Actual seawater uranium extraction performance test:
[0053] The uranium extraction capacity of I-CNF aerogel in natural seawater was measured in a simulated system using a circulating pump to simulate ocean waves. The results showed that the amount of uranium adsorbed by I-CNF aerogel increased linearly with the adsorption time, reaching 6.51 mg g in 12 days. -1 After 24 days in unfiltered natural seawater, the I-CNF aerogels obtained 9.46 mg g -1 The high uranium adsorption capacity of I-CNF aerogel is 2.57 times that of NI-CNF aerogel, and only decreased by 8.69% compared with the adsorption in filtered natural seawater, which proves the high anti-biological fouling ability of I-CNF aerogel in natural seawater environment. More importantly, the high partition coefficient K of I-CNF aerogel for uranyl ions D is 3.62×10 6 mL g -1 , an increase of 213.69% compared with NI-CNF aerogel. In addition, the adsorption capacity of I-CNF aerogel for uranium is 19.01 times that of vanadium, which is 2.13 times that of NI-CNF aerogel ( Figure 7). The binding selectivity of I-CNF aerogels for uranium is much higher than that of most other uranium adsorbents, which is attributed to the synergistic effect of precisely pre-organized coordination functional groups and immobilized coordination spatial structures achieved by ion imprinting and subsequent covalent chemical cross-linking. These results demonstrate the significant advantages of I-CNF aerogels in uranium extraction, including uranium adsorption capacity, uranium adsorption speed, mechanical properties, binding selectivity, and antifouling ability, greatly improving the application potential of I-CNF aerogels in natural seawater.
[0054] In summary, the ion-imprinted cellulose-based aerogel material for extracting uranium from seawater prepared by the method provided by the present invention is light in weight, has excellent mechanical properties, has high selectivity for uranium, has fast adsorption speed, high adsorption capacity, and has anti-biological fouling activity. The low raw material cost and the excellent reusability of the aerogel greatly reduce the cost of extracting uranium from seawater.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater, characterized in that: The following steps are involved: S101: The cellulose nanofiber suspension is sequentially oxidized with sodium periodate and cross-linked with polyethyleneimine, and then freeze-dried to obtain CNF-OP aerogel; S102: adding CNF-OP aerogel to a uranium-containing solution and shaking, then adding epichlorohydrin for cross-linking reaction, and then eluting uranyl ions to obtain ion-imprinted CNF aerogel, wherein the mass ratio of epichlorohydrin to CNF-OP aerogel is 5; The mass concentration of the cellulose nanofibers is 1 wt %, and the volume is 10 mL; the polyethyleneimine solution is 0.14 g, the mass concentration is 50 wt %, and the stirring time is 30 min.
2. The method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater according to claim 1, characterized in that: The CNF-OP aerogel weighs 0.1 g and the epichlorohydrin weighs 0.5 g.
3. The method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater according to claim 1, characterized in that: In the step S102, the cross-linking reaction temperature is 60° C. and the reaction time is 4 h.
4. The method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater according to claim 1, characterized in that: The amount of sodium periodate added was 0.024 g, and the stirring time was 30 min.
5. The method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater according to claim 1, characterized in that: The concentration of the uranium-containing solution is 2.5 g L −1 , volume is 20 mL.
6. The method for preparing an ion-imprinted cellulose-based aerogel material for extracting uranium from seawater according to claim 1, characterized in that: The eluent was a mixed solution of 1 M sodium carbonate and 0.1 M hydrogen peroxide.
7. An ion-imprinted cellulose-based aerogel material for extracting uranium from seawater, characterized in that: Prepared according to any one of claims 1 to 6.